Technology and society: Its contribution to the emergence of computational thinking - Cavalcante, Elizabeth de Araujo (Seven Editora, 2024)
Nowadays, technology has gained more space in our society and has increasingly been part of our routines. And when we talk about technology, it does not mean reducing it only to the use of computers and machines, because historically this term is broad and comprehensive. The modern and postmodern periods are important milestones in the history of the relationship between technology and society. The modern period, which extends from the sixteenth to the nineteenth century, was marked by the development of science and technology. The Industrial Revolution, for example, was a time of great technological advances, which had a profound impact on society. In the postmodern period, technology is becoming increasingly complex and fast-paced. This is driving significant changes in society, such as the globalization of the economy, the rise of popular culture, and the emergence of new social movements. One of the main contributions of technology to society is the emergence of computational thinking. Computational thinking is a way of thinking that is based on the principles of computing. It involves the ability to solve problems, think logically and creatively, and communicate ideas clearly and concisely Based on the understanding that modernity is born with the integration of science with technique, and that postmodernity questions this integration with broader conceptualizations and understandings, this article discusses the relationship between technology and society, focusing on the contribution of technology to the emergence of computational thinking. Technology is playing a key role in the development of computational thinking by providing people with tools, opportunities, and incentives to think computationally. Computational thinking is an essential skill for success in the modern world, and technology is helping people develop it. DOI:https://doi.org/10.56238/sevened2024.014-026